reliability of cause-of-death coding in The Netherlands - Harteloh, Peter; de Bruin, Kim; Kardaun, Jan (European journal of epidemiology, 2010)
Cause-of-death statistics are a major source of information for epidemiological research or policy decisions. Information on the reliability of these statistics is important for interpreting trends in time or differences between populations. Variations in coding the underlying cause of death could hinder the attribution of observed differences to determinants of health. Therefore we studied the reliability of cause-of-death statistics in the Netherlands. We performed a double coding study. Death certificates from the month of May 2005 were coded again in 2007. Each death certificate was coded manually by four coders. Reliability was measured by calculating agreement between coders (intercoder agreement) and by calculating the consistency of each individual coder in time (intracoder agreement). Our analysis covered an amount of 10,833 death certificates. The intercoder agreement of four coders on the underlying cause of death was 78%. In 2.2% of the cases coders agreed on a change of the code assigned in 2005. The (mean) intracoder agreement of four coders was 89%. Agreement was associated with the specificity of the ICD-10 code (chapter, three digits, four digits), the age of the deceased, the number of coders and the number of diseases reported on the death certificate. The reliability of cause-of-death statistics turned out to be high (>90%) for major causes of death such as cancers and acute myocardial infarction. For chronic diseases, such as diabetes and renal insufficiency, reliability was low (<70%). The reliability of cause-of-death statistics varies by ICD-10 code/chapter. A statistical office should provide coders with (additional) rules for coding diseases with a low reliability and evaluate these rules regularly. Users of cause-of-death statistics should exercise caution when interpreting causes of death with a low reliability. Studies of reliability should take into account the number of coders involved and the number of codes on a death certificate.